Properties of soil under rotational grazing system submitted to turkey litter application - Pinto, Flávio Araújo; dos Santos, Franciane Lemes; Terra, Flávia Dias; Ribeiro, Diego Oliveira; Jardim Sousa, Renata Rodrigues; de Souza, Edicarlos Damacena; Carbone Carneiro, Marco Aurélio; Paulino, Helder Barbosa (Pesquisa agropecuária tropical, 2012)
Poultry litter applications can improve biological, physical, and chemical soil attributes. This study aimed at evaluating the effect of sequential turkey litter doses on properties of soil under a rotational grazing system with Brachiaria decumbens L., in Portelândia, Goiás State, Brazil. The experiment was carried out in a split-plot randomized blocks design, with four replications. Treatments consisted of turkey litter doses [no litter, 8.7 Mg ha-1 (2008), 16.5 Mg ha-1 (2008 + 2009), and 30.9 Mg ha-1 (2008 + 2009 + 2010)], for plots, with the two highest doses resulting from the accumulation of litter applications, and three sampled soil depths (0-5 cm, 5-10 cm, and 10-20 cm), for split-plots. Sequential applications of turkey litter doses improved soil fertility, increasing the pH, P, K, and base saturation rates, as well as organic carbon, total and particulate nitrogen contents, and decreasing aluminum saturation. Lower doses of turkey litter stimulated the soil microbial activity, promoting the mineralization of the organic matter particulate fraction, however, there was no effect on soil aggregation.